The Background of the siffing Arbitration Agreement (Journal of the College of Education for Women, 2019)
It is important to set the background of stiffen arbitration agreement, to understand the real reasons of the fighting. When the Syrians began to lose, raised the masahif and made their announcement, most the qurrar, and so no need to continued fighting. In their view all that remained was the matter of drawing up formal peace with Ali, Muamiya; Ali would recognize as Amir al-muminin by both Syrian and Iraqis. The most of the Iraqisfavored settlement for different persons, for example-A'shath, the most power full of the clan leaders of Rabia, his interest by insuring that neither Ali nor Muawiya gained a clear advantage was more out spoken he told Ali that not a single yawned would fight for him if he did not accept their proposal.